APPLICATION OF SIX SIGMA IN THE EVALUATION AND IMPROVEMENT OF BIOCHEMISTRY TESTING PERFORMANCE AT THONG NHAT HOSPITAL - Thị Thanh Đông, Đỗ; Thị Nhạn, Nguyễn; Kiến Đức, Ngô; Hoàng Lâm, Lê; Thị San, Nguyễn; Đình Thanh, Lê (Journal of Health and Aging, 2025)
The survey aimed to evaluate and improve the performance of testing methods of 10 biochemistry assays on AU5800 (Beckman Coulter) and cobas c503 (Roche Diagnostics) by Sigma metrics. Cross-sectional study. Ten biochemistry assays: glucose, urea, creatinine (Jaffe), cholesterol, triglycerides, AST, GGT, uric acid, HDL-Cho, total bilirubin. Collect internal and external inspection data on 2 devices under the same laboratory conditions, same test materials, at the same time from January to March 2024, calculate Sigma value. Evaluate performance and take improvement action on low-performing tests. On the AU5800 analyzer, 5 out of 10 tests (urea, creatinine, cholesterol, HDL-cholesterol, and total bilirubin) had Sigma values less than 3; 2 out of 10 tests (glucose and AST) had Sigma values between 3 and 6; and 3 out of 10 tests (triglycerides, GGT, and uric acid) had Sigma values greater than 6. On the Cobas c503 analyzer, 1 out of 10 tests (creatinine) had a Sigma value less than 3; 4 out of 10 tests (urea, cholesterol, AST, and total bilirubin) had Sigma values between 3 and 6; and 5 out of 10 tests (glucose, triglycerides, GGT, uric acid, and HDL-cholesterol) had Sigma values greater than 6. The tests with “acceptable to excellent” performance accounted for 50% on the AU5800 analyzer and 90% on the Cobas c503. The creatinine test (Jaffe method) showed “not good” performance on both systems. After improvement by switching to the enzymatic method on the c503 system, its performance changed from “not good” to “excellent.” On the AU5800 system, the performance of the creatinine (Jaffe) test improved from “not good” to “good".